Effects of vaccination against COVID-19 on the emotional health of older adults - Alarcon-Ruiz, Christoper A. (2022)
Background: The COVID-19 pandemic significantly impacted the mental and emotional health of the elderly, especially those from low to middle-income countries. However, COVID-19 vaccination may reduce this influence. Therefore, we aimed to estimate the effect of vaccination against COVID-19 on the emotional health of older adults. Methods: We selected a national, random, and stratified sample of non-hospitalized adults aged 60 to 79 years from Peru who intended to receive or had already received the COVID-19 vaccine during recruitment. During June and July 2021, the assessed outcomes were the fear, anxiety, and worry about COVID-19, general anxiety, and depression at baseline and after a month. We estimated the adjusted odds ratios (aOR) and 95% confidence intervals (95% CI) for each altered emotional health outcomes in those who had one and two doses, compared with those who were not vaccinated using multilevel logistic regression with mixed effects. Results: We recruited 861 older adults with 20.8% of loss to follow-up. At baseline, 43.9% had received only one dose of the vaccine, and 49.1% had two doses. In the analysis during follow-up, those who had two doses had less fear (aOR: 0.19; CI 95%: 0.07 to 0.51) and anxiety to COVID-19 (aOR: 0.45; CI 95%: 0.22 to 0.89), compared to unvaccinated. We observed no effects in those with only one dose. Conclusions: Two doses of COVID-19 vaccination in older adults improves their perception of COVID-19 infection consequences. This information could be integrated into the vaccination campaign as an additional beneficial effect.